2021
DOI: 10.24171/j.phrp.2021.0180
|View full text |Cite
|
Sign up to set email alerts
|

Social determinants of adherence to COVID-19 preventive guidelines: a comprehensive review

Abstract: Adherence to coronavirus disease 2019 (COVID-19) preventive guidelines (ACPG) is an important strategy to control the COVID-19 pandemic effectively. The present study aimed to identify and summarize the social determinants of ACPG among the general population. A comprehensive review was performed from December 2019 to February 2021 through searching electronic databases. Two independent reviewers assessed and selected relevant studies. Next, the characteristics and main findings of the included studies were su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
35
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(37 citation statements)
references
References 76 publications
2
35
0
Order By: Relevance
“…Socio-demographics characteristics are associated with adherence, however they only partly explain adherence to preventive measures. A comprehensive review identified and summarized factors of adherence to COVID-19 preventive measures [ 48 ]. These include: “individual socio-demographic and behavioural factors, living and working conditions, COVID-19 knowledge, attitudes and risk perception, exposure to sources and information level, leisure activities, social support, trust, social norms, psychosocial well-being, socio-economic position, and the socio-economic and political context.”(48) Adherence to COVID-19 preventive measures can be increased if we understand better the perception of preventive measures and the challenges of appropriating them in daily life.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Socio-demographics characteristics are associated with adherence, however they only partly explain adherence to preventive measures. A comprehensive review identified and summarized factors of adherence to COVID-19 preventive measures [ 48 ]. These include: “individual socio-demographic and behavioural factors, living and working conditions, COVID-19 knowledge, attitudes and risk perception, exposure to sources and information level, leisure activities, social support, trust, social norms, psychosocial well-being, socio-economic position, and the socio-economic and political context.”(48) Adherence to COVID-19 preventive measures can be increased if we understand better the perception of preventive measures and the challenges of appropriating them in daily life.…”
Section: Discussionmentioning
confidence: 99%
“…These include: "individual socio-demographic and behavioural factors, living and working conditions, COVID-19 knowledge, attitudes and risk perception, exposure to sources and information level, leisure activities, social support, trust, social norms, psychosocial well-being, socio-economic position, and the socio-economic and political context." (48) Adherence to COVID-19 preventive measures can be increased if we understand better the perception of preventive measures and the challenges of appropriating them in daily life. Studies have shown that adherence to COVID-19 preventive measures is increased if people have adequate knowledge of how SARS-CoV-2 infection spreads, agree with mandatory mask use and perceive the situation as being at high risk for themselves or others [15], as well as believe in the effectiveness of preventive measures [49].…”
Section: Discussionmentioning
confidence: 99%
“…The results of Khajehnasiri et al's study also showed that depression, financial problems, the experience of drug side effects and disease, memory problems, simultaneous use of several drugs, and complex treatment regimens were the most important barriers to adherence to the treatment regimens of diabetic patients [14]. Shush- [6].…”
Section: Introductionmentioning
confidence: 99%
“…The incidence and mortality of COVID-19 are increasing daily, so by December 20, 2021, more than 274 million cases and more than 5 million and 350 thousand deaths have been reported [5]. COVID-19 has affected individuals' health and quality of life, especially those suspected of having the disease [6]. On the other hand, observing the COVID-19 disease prevention guideline is a critical way to control the COVID-19 pandemic [7].…”
Section: Introductionmentioning
confidence: 99%
“…Finally, behaviours can be motivated by existing values or beliefs, a personal belief in the efficacy or importance of a behaviour, its impact on their identity and their ability to overcome existing habits or unconscious processes [4]. Beyond this behaviour system, broader structural factors including the environmental, political, social and cultural contexts can also influence an individual's experience of quarantine or isolation [5]. Identifying, understanding and responding to barriers and enablers to quarantine and isolation behaviours is critical to developing strategies to enhance participation and reduce adverse health outcomes.…”
Section: Introductionmentioning
confidence: 99%